Physical Activity as an Adjunctive Intervention for Adults with ADHD: A Narrative Review - Zybert, Aleksandra; Nowiński, Igor; Ocicki, Dawid; Bojarski, Michał; Kwiatkowski, Michał; Musielak, Michał; Kobryń, Iga; Kobryń, Pola; Borowska, Aleksandra; Grabowski, Jakub (Journal of Education, Health and Sport, 2026)
Background: Attention-deficit/hyperactivity disorder (ADHD) often persists into adulthood and is associated with executive dysfunction, emotional dysregulation, and reduced quality of life. As pharmacological treatment may not be sufficient for all patients, adjunctive non-pharmacological strategies are needed. Aim: This narrative review summarises evidence on the effects of physical activity on ADHD symptoms and cognition in adults. Material and Methods: PubMed and Scopus were searched, with manual reference screening. English-language studies published up to May 2026 were included, prioritising randomised trials, experimental studies, systematic reviews, and meta-analyses on physical activity in adults with ADHD. Results: Physical activity may improve selected outcomes in adults with ADHD, especially inhibitory control, the most consistently supported cognitive domain. Benefits have also been reported for attention, symptom severity, sleep, and quality of life, although findings remain heterogeneous. Adult-specific evidence remains limited compared with paediatric and mixed-age ADHD literature. Acute and longer-term interventions appear promising, but the evidence is limited by small samples, diverse protocols, and variable outcome measures. Conclusions: Physical activity is a biologically plausible and promising adjunctive strategy for adult ADHD, but it should not replace established pharmacological or psychosocial treatments. Further high-quality trials are needed to define optimal exercise protocols, long-term clinical relevance, and its role in multimodal ADHD care. Keywords: Attention Deficit Disorder with Hyperactivity; Adult; Exercise; Exercise Therapy; Executive Function; Inhibitory Control